Elaboração e aplicação de índice para avaliação do saneamento e saúde ambiental (ISSA) - Shibasaki, Karina (Universidade Federal de São Carlos, 2022)
The accelerated urban growth has brought into evidence the idea of sustainable development, which presents many challenges to be achieved and maintained in municipalities. Because of this, public management must be integrated with the use of tools to support the decision-making of public administrators. In this sense, the usefulness of indexes that address sanitation and environmental health is important for the achievement of sustainable development. Therefore, the objective of this study was to elaborate an index to evaluate the sanitary and environmental conditions in the municipality. The methodological procedures consisted of 12 (twelve) steps, which included a bibliographic survey, identification of indicators related to environmental health and sustainable development, structuring of a conceptual model (ISSA) after indicator selection criteria (C1 - to be useful, C2 - to be easy to understand, C3 - being feasible, C4 - being measurable), consultation with experts to verify the weights among the indicators by the Analytic Hierarchy Process (AHP) method, application of the ISSA in municipalities of the Baixo Pardo / Grande Watershed (UGRHI 12), comparison between Alvares' ISA (2020) and ISSA, and finally the analysis of the results. The results show that the ISSA is composed of 18 sub-indicators divided into 7 thematic axes (indicators): Water Supply, Sanitary Sewage, Solid Waste, Urban Drainage, Environmental, Public Health, and socio-economic. The consultation with the experts showed that the indicators Water Supply and Sanitary Sewage presented the highest significance, while the Public Health indicator had the lowest weight. The ISSA applied to the municipalities of UGRHI 12 indicated that 8 municipalities with medium health status and 6 municipalities with low health status. About the Watershed, a value of 48.96% (low salubrity) was obtained. In the comparison between the ISSA and ISA of Alvares (2020), there was great variance in the final values for the municipalities, and in the first index the values obtained were lower concerning the second, and for the watershed obtained Low Salubrity and Average Salubrity, respectively. Finally, in the proposed method there was the addition of variables related to the Environment and Drainage, and it is concluded that the greatest significance in the index is given by the indicators themselves, without the interference of weights, making the index more homogeneous. It is noteworthy that both methods allow improvements to be made in their methodology, and can be adopted for the evaluation of salubrity, being an efficient tool for public management.
Elaboration and application of an index to assess sanitation and environmental health
Keywords: Índice; Saneamento; Saúde Ambiental; UGRHI 12; Index; Sanitation; Environmental Health; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO; ENGENHARIAS::ENGENHARIA CIVIL; ENGENHARIAS::ENGENHARIA SANITARIA; ENGENHARIAS